Senegal : Request for a Three-Year Policy Support Instrument; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the Request for a Three-Year Policy Support Instrument (PSI) on Senegal explains economic developments. Allocations for priority spending suffered, and cash-flow problems resulted in payment delays to the private sector. The authorities intend to tackle key policy challenges under a three-year PSI. Slippages in restructuring public enterprises could raise fiscal risks and endanger banking system soundness. Weakening political resolve to implement structural reforms and address governance concerns could undermine policy credibility and reduce aid flows.